The Benefits and Challenges of Group Discussion in Syntax Project - Suhartini Syukri; A Magfira; Abdul Halim; Dewi Atikah (IAIN Kendari, 2021)
In the frame of qualitative research, this study aims to know the benefits and challenges of group discussion in Syntax project for students in EFL context in accomplishing Syntax project. The participants of this study consist of 25 students from the students of Syntax class in one of the higher educations in Kendari. The qualitative data were analyzed by questionnaire and students’ interview. The results of the research revealed that the students’ responded positively to the group discussion activity. It indicated this activity can improve students’ confidence and communication skills. Nevertheless, the students found it challenging in terms of the time allocation to finish the project as they cannot manage their time to finish the project well